Predictive performance of stress hyperglycemia ratio for poor prognosis in critically ill patients: a systematic review and dose–response meta-analysis - Lili Chen; Xiaoxue Zeng; Wenjing Zou; Meng Chen; Ya Fan; Ping Huang (European Journal of Medical Research)
Abstract Background Stress hyperglycemia ratio (SHR) refers to the ratio of blood glucose levels to glycated hemoglobin (HbA1c) levels upon admission. As a non-invasive and easily obtainable indicator, there is no systematic evidence-based medical evidence to support the value of SHR in predicting the poor prognosis of critically ill patients at present. Methods PubMed, Embase, Cochrane Library, and Web of Science databases were systematically searched with a December 20, 2024 deadline. Prospective and retrospective cohort studies were included. Two investigators independently screened studies and extracted data. The Newcastle–Ottawa scale was applied to appraise the risk of bias in the studies included. Statistical analysis was executed by means of Stata 15.1 software. Study heterogeneity was assessed with the I2 statistic. A restricted cubic spline model was leveraged for dose–response analysis. Sensitivity analyses were implemented to verify the stability of the results using the one-by-one exclusion method, and subgroup analyses were conducted with disease types. Results 39 studies involving 102,414 patients were included. The meta-analysis revealed that SHR exhibited a noticeable positive link with major adverse cardiovascular events (MACE), 30-day mortality, one-year mortality, cardiovascular mortality (CVM), and all-cause mortality (ACM) in critically ill patients. Dose–response analysis showed that a positive link of SHR with multiple mortality was noted in critically ill patients. Conclusion SHR is an independent predictor of mortality in critically ill patients, and its dynamic monitoring could provide essential support for early clinical risk stratification and intervention strategies.